Syn-tasiR-VIGS: virus-based targeted RNAi in plants by synthetic trans-acting small interfering RNAs derived from minimal precursors - Cisneros, Adriana; Alarcia, Ana; Llorens-Gámez, Juan José; Puertes, Ana; Juárez-Molina, María; Primc, Anamarija; Carbonell, Alberto (Nucleic acids research)
Synthetic trans-acting small interfering RNAs (syn-tasiRNAs) are 21-nucleotide (nt) small RNAs designed to silence plant transcripts with high specificity. Their use as biotechnological tools for functional genomics and crop improvement is limited by the need to transgenically express long TAS precursors to produce syn-tasiRNAs in vivo. Here, we show that authentic and highly effective syn-tasiRNAs can be produced from minimal, non-TAS precursors consisting of a 22-nt endogenous microRNA target site, an 11-nt spacer, and the 21 nt syn-tasiRNA sequence(s). These minimal precursors, when transgenically expressed in Arabidopsis thaliana and Nicotiana benthamiana, generated highly phased syn-tasiRNAs that silenced one or multiple plant genes with high efficacy. Remarkably, minimal but not full-length TAS precursors produced authentic syn-tasiRNAs and induced widespread gene silencing in N. benthamiana when expressed from an RNA virus, which can be applied by spraying infectious crude extracts onto leaves in a transgene-free manner. This strategy, named syn-tasiRNA-based virus-induced gene silencing (syn-tasiR-VIGS), was further used to vaccinate plants against a pathogenic virus, resulting in complete plant immunization. Our results reveal that syn-tasiRNA precursors can be significantly shortened without compromising silencing efficacy, and that syn-tasiR-VIGS represents a versatile, scalable, and nontransgenic platform for precision RNA interference and antiviral vaccination in plants.
Gesehen am 02.10.2025